2018
DOI: 10.1200/jco.2018.36.34_suppl.143
|View full text |Cite
|
Sign up to set email alerts
|

Frontline oncology care team primary palliative symptom guideline education, the oncology care model, and emergency department visits.

Abstract: 143 Background: The Oncology Care Model (OCM) is a novel 5-year quality-based Oncology payment and care delivery program established by the Centers for Medicare & Medicaid Service in 2016. OCM prioritizes high-quality, coordinated care for patients undergoing chemotherapy (chemo pts.) Participating centers provide augmented services to enhance care and meet quality goals. Challenging symptoms (sxs) are common among chemo pts and may lead to hospitalization and decreased quality of life. Specialist palliat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…With cancer care costs especially on the increase, the OCM, inclusive of a shared-savings component in a specialty with prescribing discretion over consequential high-cost care choices, represents a novel environment to evaluate these programs. This nonrandomized controlled study adds to the emerging literature by finding that first-year OCM participation was associated with lower office-based costs. However, consistent with prior research on similar programs, we also found that these savings were largely offset by the costs of these programs …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…With cancer care costs especially on the increase, the OCM, inclusive of a shared-savings component in a specialty with prescribing discretion over consequential high-cost care choices, represents a novel environment to evaluate these programs. This nonrandomized controlled study adds to the emerging literature by finding that first-year OCM participation was associated with lower office-based costs. However, consistent with prior research on similar programs, we also found that these savings were largely offset by the costs of these programs …”
Section: Discussionmentioning
confidence: 81%
“…A cross-sectional analysis by Parikh et al 16 found that oncologists participating in the OCM varied in their demographic characteristics, care intensity, and exposure to alternative models compared with nonparticipating oncologists in ways that practice-level analyses might meaningfully miss, motivating physician-level analysis. While there is some early suggestive evidence that the OCM altered hospitalization rates 17 and other descriptive or non-peer-reviewed work, 16,[18][19][20][21][22][23][24][25][26][27] there remain few assessments of the OCM's potential effects on care choices. 14 This study evaluates whether OCM participation was associated with clinician behavior within the context of their practices.…”
Section: Introductionmentioning
confidence: 99%